2010
DOI: 10.1007/s12088-010-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple antibiotic resistance indexing of coliforms to identify high risk contamination sites in aquatic environment

Abstract: Bacteriological analysis of the water samples collected from upstream, midstream and downstream points along the bank of the river revealed high populations of Escherichia coli, Citrobacter freundii, Citrobacter diversus, Enterobacter aerogens and Klebsiella species. All these isolates were screened against eight antibiotics to determine the prevalence of multiple antibiotic resistance among isolates at different sites of the river. The study revealed that multiple antibiotic resistance was prominently seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 10 publications
2
44
0
2
Order By: Relevance
“…MAR range 0.1-0.7, 0.3-0.9 and 0.35-1.0 were recorded among the isolates from site I (polluted), site II (polluted) and site III (less polluted receiving the treated water near the treatment plant), respectively. No significant difference among the isolates from polluted and less polluted sites was observed regarding their antibiotic (Chitanand et al, 2010) All E. coli strains isolated from river and polluted waters show a high incidence of MAR phenotype. Many investigators have recognized that wastewater treatment plants are the principal recipients of enteric bacteria with multiple antibiotic resistance (Selvaratnum and Kuberger, 2004) and an important site for horizontal gene transfer, by containing nutrients and high concentrations of microorganisms (Sloan et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…MAR range 0.1-0.7, 0.3-0.9 and 0.35-1.0 were recorded among the isolates from site I (polluted), site II (polluted) and site III (less polluted receiving the treated water near the treatment plant), respectively. No significant difference among the isolates from polluted and less polluted sites was observed regarding their antibiotic (Chitanand et al, 2010) All E. coli strains isolated from river and polluted waters show a high incidence of MAR phenotype. Many investigators have recognized that wastewater treatment plants are the principal recipients of enteric bacteria with multiple antibiotic resistance (Selvaratnum and Kuberger, 2004) and an important site for horizontal gene transfer, by containing nutrients and high concentrations of microorganisms (Sloan et al, 2014).…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, Tambekar et al, [15] reported that the thermotolerant E.coli isolated from the drinking water from salinity affected villages of Purna River basin of Vidarbha were 75% human fecal origin and 25% were non human fecal origin. The study done by Chitanand et al, [16] showed that multiple antibiotic resistances was prominently seen in coliforms at downstream sites while it was low in coliforms at up streams sites along the bank of river and the differences in MAR indices provide a method for distinguishing high risk contamination sites in aquatic environment. The antibiotic resistance index for detected thermotolerant E.coli in ODNF (Open defecation not free) villages were found higher than in ODF (open defecation free) villages [17].…”
Section: Resultsmentioning
confidence: 99%
“…Sebaliknya menurut Rocha et al (2016) sebanyak 70 strain vibrio dari sampel air dan sedimen di lingkungan tambak udang bersifat resisten terhadap salah satu antibiotik seperti siprofloksasin dan kloramfenikol. Beberapa strain bakteri yang bersifat resisten terhadap siprofloksasin merupakan permasalahan serius saat ini karena antibiotik ini merupakan pilihan antibiotik yang cukup baik untuk beberapa bakteri gram negatif (Chitanand, Kadam, Gyananath, Totewad, & Balhal, 2010).…”
Section: Pola Resistensi Bakteri Terhadap Antibiotikunclassified
“…Chitanand et al (2010) melaporkan bahwa indeks MAR kisaran rendah (0,15) di wilayah upstream mengindikasikan adanya risiko kontaminasi rendah. Sementara indeks yang moderat berada di wilayah midstream, dan indeks MAR yang lebih tinggi di wilayah down stream.…”
Section: Nilai Indeks Mar (Multiple Antibiotic Resistance)unclassified